Higher Expression of Activating Receptors on Cytotoxic NK Cells is Associated with Early Control on HIV-1C Multiplication - Kulkarni, Archana Gopal; Paranjape, Ramesh Shivram; Thakar, Madhuri Rajeev (Frontiers in Immunology, 2014)
Natural killer (NK) cells may be important in modulating HIV replication in early course of HIV infection. The effector function of NK cells is finely tuned by a balance between signals delivered by activating and inhibitory receptors. However the influence of expression of these receptors on the early course of HIV replication and subsequent disease progression is not explored in context of HIV-1 C infection. The expression pattern of activating (NKp46,NKp44, NKp30, NKG2D,NKG2C) and inhibitory (CD158b, NKG2A and ILT2) receptors was determined in 20 patients with recent HIV-1 C infection within 3-7 months of acquiring HIV infection and was compared with the expression pattern in individuals with progressive (N=12), non progressive HIV-1C infection (LTNPs, N=12) and healthy seronegative individuals (N=20). The association of the expression of these receptors on the rate of disease progression was assessed using viral load set point in recently infected individuals as a marker of disease progression. The study showed that higher cytotoxic potency of NK cells was associated with low viral load set point in recent HIV infection (r=-0.701; p=0.0006) and higher CD4 counts (r=0.720; p=0.001). The expression of activating receptors (NKp46, NKp30 and NKG2D) on cytotoxic NK cells but not on regulatory NK cells was significantly associated with low viral set point(p< 0.01) and viral load in LTNPs (p< 0.01).The study also indicated that cytotoxic NK cells might show the ability to specifically lyse HIV infected CD4 cells. This data collectively showed that early and sustained higher expression of activating receptors on cytotoxic NK cells could be responsible for increased cytotoxicity, reduced viral burden and thus delaying the disease progression. The study to identify the influence of HIV on the molecular mechanism of the expression of these receptors will be helpful in further understanding of NK cell mediated control in early HIV infection.